Increasing economic opportunity and competitiveness in the EU: The role of micro-credentials - Matthias Bauer; Elena Sisto; Renata Zilli (European Centre for International Political Economy (ECIPE), 2024)
As Europe experiences rapid technological advancements driven by innovations such as automation, Artificial Intelligence, and the Internet of Things, the demands on the workforce are evolving at an unprecedented pace. This shift has exposed the limitations of traditional education systems, which struggle to equip individuals with the skills needed to thrive in a dynamic job market. Micro-credentials - short, targeted learning experiences - are emerging as a powerful tool to bridge this gap, enabling a more skilled and agile workforce that can adapt to changing industry needs. Europe's labour market is shifting towards valuing specific skills that do not necessarily require traditional university degrees. Skillsbased hiring is broadening talent pools and creating more opportunities, especially for those without formal education, women in under-represented fields, and younger generations. This change calls for a reevaluation of candidate assessment methods and underscores the importance of Continuing Vocational Education and Training (CVET) to help workers stay competitive in an evolving job market.
Keywords: 330